Analysis of severe industrial accidents caused by hazardous chemicals in South Korea from January 2008 to June 2018. (April 2020) - Jung, Seungho; Woo, Jongkwon; Kang, Chankyu
Highlights: This study investigates chemical accidents that occurred between January 2008 and June 2018 in South Korea. 76.1% of chemical accidents were caused by human error in South Korea. Large-scale enterprises experienced the largest number of industrial accidents during maintenance work. Fire and explosion accounted for 72% of all CPI accidents, of which 32.4% were ignited by static electricity. Chemical accidents mostly occurred in storage tanks, chemical reactors, and mixing tanks. Abstract: Major accidents in the chemical process industries are relatively rare, but the resulting harm to workers, property loss, business interruption, and the environment are very serious. This study investigates chemical accidents that occurred between January 2008 and June 2018 in South Korea, and proposes ways to prevent similar accidents from occurring by analyzing the main causes of these accidents. Nine core concepts were drawn from the analyses comparing chemical accidents in South Korea: (1) current casualties by type of worker, (2) how the scale of the enterprise affects the disaster, (3) chemical accidents by type of occurrence, (4) analysis of ignition sources, (5) chemical accidents by CPI facilities, (6) human and technical error, (7) chemical accidents by work situation, (8) chemical accidents by non-compliance of process safety management (PSM) standards, and (9) chemical accidents by hazardous materials. Although there have been no recent occurrences of large chemical accidents since 2017 due to various factors, our results indicate that the past frequency of such accidents area serious concern in South Korea. Understanding the root causes of these accidents can help to prevent the recurrence of similar accidents and to strengthen preventative measures in chemical plants.